TRENDS IN THE DEVELOPMENT OF KNOWLEDGE ASSESSMENT TECHNOLOGIES IN POSTGRADUATE TRAINING SYSTEMS - Mintser, O.P.; Mokhnachov, S. I.; Shevchenko, Ya. O. (Medical Informatics and Engineering, 2022)
Materials and methods. The analyzed test results of 77 graduate students who studied at Shupyk National Healthcare University of Ukraine during 2021-2022. Relevance and pertinence were assessed by cognitive methods. Pearson's coefficient of variation was used as an indicator of validity. Mathematical data processing was performed on a personal computer using statistical programs Statistica, Microsoft Excel 2016, Statgraphics for Windows. Results. The features of the analysis were the accentuation of knowledge verification and the effectiveness of knowledge transfer regarding the technology of diagnosing human conditions, monitoring health conditions, forecasting, identifying risks and confounders using a complex of clinical, instrumental and laboratory research methods. Close attention was paid to mastering the basic concepts of mobile and personalized medicine, systemic biomedicine, as well as communication and cognitive problems in health care. The study of the principles of transdisciplinarity in health care was considered from new positions. Conclusions. The effectiveness of mobile training of post-graduate students was investigated. It is shown that the indicators of the quality of training during mobile training have a tendency to decrease from 88.8±5.3 % to 84.0±5.4 % (statistically, however, not probable, p>0.05). There is also an incredible decrease in the values of the indicators of validity, pertinence and relevance of knowledge acquisition, as well as the integral quality of knowledge transfer during mobile learning (p>0.05). It is extremely important to develop such evaluation tasks that correspond to a high-level system, effectively using the evaluation structure.